Implementation Strategy of Collaborative Academic Supervision of High School Principals in Pidie Regency - Sarah, Siti; Ilyas, Mukhlisuddin; Rizki, Sari (Yayasan Pendidikan dan Kemanusiaan Hurriah Aceh, 2025)
This study examines the implementation of collaborative academic supervision by senior high school principals in Pidie Regency and its impact on teacher performance. Using a qualitative, descriptive approach with in-depth interviews, field observations, and document analysis at SMAN 1 Mutiara and SMAN 2 Mutiara, the research identifies three key phases: planning, implementation, and follow-up. In the planning phase, principals and teachers jointly design supervision agendas addressing actual learning needs. Implementation emphasizes dialogue and reflection through classroom observations, group discussions, and individualized mentoring. Follow-up activities include training, workshops, and peer supervision to sustain pedagogical improvement. Findings indicate that collaborative academic supervision enhances teachers’ professional competencies in lesson planning, classroom management, innovative methodologies, and learning assessment. It also fosters a collaborative culture, dynamic learning environments, and greater teacher motivation for ongoing development. The study offers theoretical insights for developing collaboration-based supervision models and practical guidance for principals, supervisors, and policymakers in crafting effective, context-sensitive supervision strategies to improve educational quality.